DESAIN PENGEMBANGAN MODEL BISNIS PADA START-UP SYARIHUB DI SURABAYA - Afandi, Muh. Asrori (Arthavidya Jurnal Ilmiah Ekonomi, 2021)
Abstract : In the growing times, the competition in start-up so tight. As start-up whom have much capital modals, they will give rebate for customerto buy their product services, but as start-up whom less capital modals, they should think and make value added for customer to make them interest and want to buy their product services. This study aims to give recomendation for start-up such as syarihub to increase profit with Business Model Canvas (BMC) approach. This study uses qualitative methods while formulating strategies by observe and use in depth interview, and then analyzing them using five forces and Business Model Canvas. The result of the study have found that : add value proposition star-up syarihub with education and society program such as empower woman, empower disability, religion education, awareness of parenting, private lesson, and fun learning for kid. Key word: Start-Up, Five Forces, Business Model Canvas, Syarihub.